Reporting Recession in Online News Worldwide: Spain as a Test-case. - Cabrera-González, María de los Ángeles; Segev, Elad; Blondheim, Menahem (My University, 2014)
This study measures the presence of Spain in online news worldwide as an example of the significance of economic news in a globalizing, interdependent environment. Employing the ´Global Salience Meter` based on a multilingual news-mining technique, Spain´s relative prominence was traced over 43 months in 35 leading news sites in 10 languages. Our findings reveal a growing online attention given to Spain, especially in the business section of European digital news outlets. Network analysis of country co-mentions finds that together with European countries, Spain is frequently mentioned together with the US and international organizations. This reflects the underlying regional and global economic structures and ties related to the European economic recession. More generally it points to the increasing connectedness of the world´s economies and the world´s online news reporting.
El artículo es resultado de la colaboración entre los autores durante una estancia de investigación de la autora principal, M.Angeles Cabrera González, en la Universidad Hebrea de Jerusalén, entre 2011 y 2013.
Keywords: Crisis económicas; Globalización (Economía); Información internacional - Recursos en Internet; International news; News mining; Online media; Economic crisis; Globalization